Silicon Naphthalocyanine Tetraimides: Cathode Interlayer Materials for Highly Efficient Organic Solar Cells. (20th July 2021) - Cai, Chunsheng; Yao, Jia; Chen, Lie; Yuan, Zhongyi; Zhang, Zhi‐Guo; Hu, Yu; Zhao, Xiaohong; Zhang, Youdi; Chen, Yiwang; Li, Yongfang
Abstract: Naphthalocyanine derivatives (SiNcTI‐N and SiNcTI‐Br) were firstly used as excellent cathode interlayer materials (CIMs) in organic solar cells, via introducing four electron‐withdrawing imide groups and two hydrophilic alkyls. Both of them showed deep LUMO energy levels (below −3.90 eV), good thermal stability (Td >210 °C), and strong self‐doping property. The SiNcTI‐Br CIM displayed high conductivity (4.5×10 −5  S cm −1 ) and electron mobility (7.81×10 −5  cm 2  V −1  s −1 ), which could boost the efficiencies of the PM6:Y6‐based OSCs over a wide range of CIM layer thicknesses (4–25 nm), with maximum efficiency of 16.71 %. Abstract : SiNcTI‐Br with strong self‐doping property, high conductivity, and high electron mobility is an excellent cathode interlayer material. The interlayer boosts the power conversion efficiency of PM6:Y6‐based OSCs to 16.71 %. It is the first naphthalocyanine derivative used as interlayer material in optoelectronic devices.